A Employee Readiness and Implementation of Risk Management in the Work Rule Changes / Standard Operation Procedure and Its Effect on Performance - Renwarin, Joseph M J (PT. BERBAGI TEKNOLOGI SEMESTA, 2024)
The purpose of this research is to understand the effect of employee readiness and Risk Management Implementation at pharmacy company Group in facing SOP/work rules changes and its effect to the performances. This research is a quantitative research that using survey method conducted to the Personnel that implementing Risk Management at entities in Pharma Company Group. Sample taken as a Purposive - Non probability Sampling. Research result shows that there is no significant influence between employees readiness with SOP/work rules changes. Risk Management Implementation will give a significant affect to SOP/Work rules changes. Employee readiness and risk management implementation simultaneously give a significant affect to SOP/ Work rules changes. SOP/ Work rules changes will give a significant affect to performances.